2020
DOI: 10.1039/c9tc05817f
|View full text |Cite
|
Sign up to set email alerts
|

Calix[4]resorcinarene-based hyper-structured molecular thermally activated delayed fluorescence yellow-green emitters for non-doped OLEDs

Abstract: A series of novel hyper-structured molecular (HSM) thermally activated delayed fluorescent (TADF) emitters, in which the TADF units and host units are bound together into one inactive core through flexible linkages, were designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…These higher quantum yields are maintained at both high doping concentrations and in concentrated solution, proving that cyclization is an effective strategy for suppressing fluorescent quenching. Other OLEDs devices fabricated on the basis of emissive resorcinarenes, 315 CPPs, 316 cyclometaphenylenes, 19,317 calixarenes 82,318 or cyclophanes incorporating dibenzofuran, 319 carbazole, 320 fluorene, 321 dibenzo[ a , j ]phenazine units 322 have also been reported.…”
Section: Applicationsmentioning
confidence: 99%
“…These higher quantum yields are maintained at both high doping concentrations and in concentrated solution, proving that cyclization is an effective strategy for suppressing fluorescent quenching. Other OLEDs devices fabricated on the basis of emissive resorcinarenes, 315 CPPs, 316 cyclometaphenylenes, 19,317 calixarenes 82,318 or cyclophanes incorporating dibenzofuran, 319 carbazole, 320 fluorene, 321 dibenzo[ a , j ]phenazine units 322 have also been reported.…”
Section: Applicationsmentioning
confidence: 99%
“…74 In platforms of the resorcinarene type, chromophores and compounds with thermally activated delayed fluorescence (TADF) were incorporated (Scheme 8). Liu et al 12 in 2016 and Wang et al in 2020 79 reported resorcinarene conjugates obtained with click chemistry (CuAAC) using as a functionalized platform octaalkylcalix [4] of compound 59, it was obtained with a yield of 40% compared to compound 60, which exhibited a yield of 75%. This type of compound can have applications in the generation of new photosensitive materials.…”
Section: Click Chemistrymentioning
confidence: 99%
“…74 In platforms of the resorcinarene type, chromophores and compounds with thermally activated delayed fluorescence (TADF) were incorporated (Scheme 8). Liu et al 12 in 2016 and Wang et al in 2020 79 reported resorcinarene conjugates obtained with click chemistry (CuAAC) using as a functionalized platform octaalkylcalix [4]resorcinarene 58. In both syntheses, the copper(I) species was used directly, using CuBr and PMDETA stabilizer in DMF for 24 h. For the case of compound 59, it was obtained with a yield of 40% compared to compound 60, which exhibited a yield of 75%.…”
Section: Click Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence and chromogenic techniques are considered sensitive, selective, and economical methods for the detection of charged or neutral species at a low level [5][6][7]. Recently, the numbers of uorophores and chromophores have been developed based on the supramolecular system as well as small molecules [8][9][10][11][12][13][14][15][16][17]. Among supramolecular based sensors, Calixarene-based molecules have received intense attention in the last few years in different elds of applications as carriers, sensors, and catalyst [14,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%